Majoritarian politics and hate crimes against religious minorities in India, 2009-2018 - Deepankar Basu (University of Massachusetts, Department of Economics, 2019)
Using a state-level panel data set on the incidence of hate crimes in India, this paper implements difference in difference (DID) and triple difference in difference (DDD) research designs to estimate the causal impact of the right-wing BJP's win in the 2014 parliamentary elections on hate crimes against religious minorities (Muslims, Christians and Sikhs). Comparing the periods 2009-13 (pre-election) and 2014-18 (post-election), I find that BJP's electoral victory caused an increase in the incidence of hate crimes against religious minorities in India.
Keywords: D72; D74; 330; minorities; hate crimes; electoral outcomes; difference in difference